The effects of the Pseudomonas aeruginosa-derived pigment, 1-hydroxyphenazine, on calcium metabolism and release of primary granule enzymes from activated human neutrophils in vitro - Anderson, Ronald (University of Pretoria, 2013)
Thesis (DPhil (Medical Immunology))--University of Pretoria, 2007.